Phase-error-measurement and compensation in PLL frequency- synthesizers for FMCW sensors - II: Theory - Pichler, Markus; Stelzer, Andreas; Gulden, Peter; Seidenberger, Claus; Vossiek, Martin (IEEE Transactions on Circuits and Systems I-Regular Papers, 2007)
Synthesizers for the generation of frequency- or phase-modulated signals are required in communications, sensing, and many other fields and applications. The widespread use of phase-locked loops (PLLs) as major building blocks in current systems requires accurate models and methods for eliminating the influence of statistical and deterministic errors in the synthesized signals. We propose a novel iterative phase-error-measurement and -compensation procedure applicable in PLL-based synthesizers, for which the mathematical background is presented, and a detailed algorithmic description is given in this work. From a mathematical PLL system model and its response to a periodic excitation by the modulating signal, a method for measuring the instantaneous output signal phase and the actual transfer function of the PLL is derived. It is shown how this knowledge can advantageously be used for pre-distorting the synthesizer input signal to eliminate deterministic errors and to obtain an accurate output phase curve. © 2007 IEEE.
UnivIS-Import:2015-03-09:Pub.2007.tech.IE.LEH.phasee_7
Keywords: Chirp radar; Frequency synthesizers; Phase measurement; Phase-locked loops (PLLs)